Bladder Bleeding Due to Placenta Percreta: Report of Four Cases and Management Discussion. Issue 4 (12th October 2021) - Zhao, Huidan; Zhao, Xianlan; Liu, Chuanna; Tao, Ya; Zhou, Yan
Abstract : Abstract: Placenta percreta with bladder bleeding can occur during gestation or postpartum, posing a great threat to both mother and fetus. But it is rare and lacks standard management strategies. We reported four cases suffering from bladder bleeding caused by placenta percreta even with hemorrhagic shock admitted between January 1 st, 2011 and December 31 th, 2020 in The First Affiliated Hospital of Zhengzhou University. Clinical information, including age, gravidity and parity, ultrasound and magnetic resonance imaging manifestations, onset gestational age, bladder bleeding volume, clinical manifestations under bleeding, diagnosis, hemostatic methods, hospital stay, treatment cost, and prognosis, are presented. Two cases had bladder bleeding during the second trimester, respectively on the 22 +3 and 23 +5 weeks. Pregnancy was terminated timely. The other two cases had bladder bleeding on the 2 nd day post near-term cesarean section when activity. All the four cases achieved successful hemostasis following angiography and concomitant embolization for iliac vessels, and one of them received electrocoagulation hemostasis under cystoscopy, but failed. They all had favorable clinical outcomes and had no long-term complications. The neonatal outcome in the two cases that bladder hemorrhage occurred after near-term c-section was good. The newborns did not survive in two cases in which bladder hemorrhage occurred at the second trimester of pregnancy. Timely termination of pregnancy is recommended when such a condition develops during gestation. Diagnosis of bladder bleeding is relatively easy, for it is characterized by fast speed and large volume, with concomitant distension of the lower abdomen, blood discharge from the urethral orifice, or the indwelling catheter. Interventional embolization is an effective means to treat bladder bleeding caused by placenta percreta, while electrocoagulation hemostasis under cystoscopy must be applied with great caution. For the pregnant women with a high risk of placenta percreta, timely and accurate diagnosis should be achieved during the gestational age, and bladder bleeding should be concerned when placenta penetrates through the anterior wall of uterus.